Investigando a Acessibilidade nos Currículos de Cursos de Ensino Superior em Computação no Brasil - Camelo, Lucas Samuel S.; Silva, Ingrid M. M. da; Lima, João P. V. de; Sousa, Bruno S. de; Santos, Suzane S. dos; Mota, Marcelle P. (Anais do Workshop em Culturas, Alteridades e Participações em IHC (CAPAihc); 2023: Anais do II Workshop em Culturas, Alteridades e Participações em IHC, 2023)
As interactive computer systems and their digital electronic devices become increasingly complex and sophisticated, the inclusion of accessibility features has often been neglected both in developing these systems and their instruments and in teaching during the formation of Computer professionals. This work seeks to map the presence of content related to digital accessibility in undergraduate courses in Brazilian public institutions, such as Computer Science, Computer Engineering, Software Engineering, Information Systems, and Degree in Computer. For this, two stages of data collection were carried out. First, we identified the active courses using the federal government’s e-MEC platform. Then, we searched for the contents of the courses’ pedagogical projects through documentary research. The results indicate that 46% of the analyzed courses include teaching about digital accessibility.